MEMPERPANJANG MASA PAJANG BUNGA POTONG KRISAN (Chrysanthemum morifolium) - Stella Kountur; Jeany Sh. Polii-Mandang; Stella Tulung (Universitas Sam Ratulangi, 2018)
ABSTRACT Â The purposes of this research is to know the utilization of the sugar preservative solvent, coconut water, vinegar and clorox towards the quality of Chrysanthemum morifolium, to know the best composition of the soaking sugar preservative solvent, coconut water,vinegar and chlorox in preserve freshness of the Chrysanthemum morifolium. This research study was conducted in the Laboratory of Plant Science, Department of Agriculture Cultivation, Universitas Sam Ratulangi Manado which start from June until August 2018. The experimental design for this research using a completely randomized design with 12 treatments and 4 repetition. The composition of preservative solvent are A : Water 1000 ml, B : Sugar 25 g/l , C : Coconut Water 40%, D : Vinegar 0,4ml / l, E : Chlorox 1 ml/l , F: Sugar 25 g/l + Coconut Water 40%, G: Sugar 25 g/l + Vinegar 0,4 ml/l, H: Sugar 25 g/l + Chlorox 1 ml/l, I: Coconut Water 40% + Vinegar 0,4 ml/l, J: Coconut Water 40% + Chlorox 1 ml/l , K: Sugar 25 g/l + Vinegar 0,4 ml/l + Coconut Water 40%, L : Sugar 25 g/l + Vinegar 0,4 ml/l + Coconut Water 40% + Chlorox 1 ml/l. The variables observed the flower freshness, the increases of the flower diameter and total of the absorbed solvent. The Sugar preservative solvent,Vinegar, Coconut Water and Chlorox had affected the age of the Chrysanthemum morifolium,Â in this case could extend the long period of Chrysanthemum morifolium. This is indicated by the treatment of Sugar 25 g/l + Vinegar 0.4 ml/l + Coconut Water 40% + Chlorox 1 ml/l which is in 20,25 days. KeywordsÂ : cut flowers, Chrysanthemum morifolium, preservative solution